Pemanfaatan Campuran Bunch Ash dan CaCO₃ dalam Proses Claybath untuk Meningkatkan Efisiensi Pemisahan Inti dan Cangkang Kelapa Sawit - Rahimah Rahimah; Wardatul Husna Irham; Bagus Satria (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2026)
The palm oil processing industry requires an efficient kernel-shell separation process to improve product quality and minimize kernel losses. One commonly used method is the claybath system that utilizes the density difference between the kernel and shell using a calcium carbonate (CaCO₃) solution. However, using large amounts of CaCO₃ can increase operational costs and generate waste. This study aims to analyze the effect of combining Bunch Ash (oil palm empty fruit bunch ash) with CaCO₃ on the effectiveness of the claybath process. The research method uses an experimental approach with five mixture compositions: 0:100, 25:75, 50:50, 75:25, and 100:0. The parameters observed include reductions in dirt content and kernel losses. The results showed that a mixture of 25% Bunch Ash and 75% CaCO₃ gave the best results with an average reduction in dirt content of 56.44% and a reduction in losses of around 86.66%. These results indicate that Bunch Ash has the potential to be a partial substitute for CaCO₃ in clay bath systems, thereby increasing process efficiency and supporting the utilization of biomass waste in the palm oil industry.